Clinical spectrum of childhood dermatoses during peak summer in a tertiary care centre - Subramaniam, Jayanthi Nagappan; Pichaachari, Saraswathy; Balakrishnan, Prithivirajan (International Journal of Research in Dermatology, 2019)
Background: Paediatric dermatoses are very common and may reflect the health and hygiene status of children. The incidence of these skin lesions is widely influenced by seasonal factors. The aim of the study was to study the spectrum of various dermatoses in summer months in children in a tertiary health care centre in north Chennai. Methods: The study included all paediatric cases up to 12 years of age attending the skin OPD of our hospital during the month of May 2018. Total numbers of patients were 975. The patients were divided into 4 categories -infants (< 1 year), toddlers (1-3 years), pre-school children (3-5 years), school going children (5-12 years) as A, B, C and D respectively. Results: Number of children seen in different groups included infants (8.20%), toddlers (23.59%), pre-school children (22.67%), school going children (45.54%) in groups A, B, C and D respectively. The most common skin disease observed comprised of pyoderma (44.18%), followed by miliaria rubra, scabies, dermatophytosis, insect bite allergy, HFMD and others with less than 1% prevalence. Conclusions: The study shows that infections were more common in the paediatric age group in summer, which can provide a suitable environment for the organisms to survive and the infections can be controlled easily by providing proper health care facilities. In order to plan better health care for children, it is mandatory to have a good idea about the existing ailments in the region.